Etat et croyance(s) dans la Bolivie « plurinationale » d’Evo Morales - Christine Delfour (Amnis)
« The Bolivian Church is the main enemy of reforms », « some sectors of the Catholic Church, the Catholic Hierarchy, are the enemies of political changes », « another faith, another religion (outside the Catholic Church), and also another church, all this is positive, my brothers and sisters ». These few quotes from Evo Morales, Bolivia’s first Indian president, illustrate, on the one hand, existing tensions between the authorities of the Plurinational State and those of the Catholic Church, and, on the other hand, the new institutional reality in matters of religion: the freedom of religion and spiritual practices and of spiritual beliefs of indigenous peoples and all other faiths. The New Political Constitution of the Plurinational State (February 2009) recognizes the State’s independence from religion, a State which « respects and guarantees the freedom of religion and of spiritual beliefs in accordance to every individual’s cosmovisions ». This represents a radical change compared with the Constitution of 1967 which, in its 3rd article, stipulates that « the State recognizes and supports the Roman Catholic Apostolic religion ». We will investigate, on the one hand, the relationship between the Church and the Republican State, and, on the other hand, we will analyse the place occupied by beliefs (rites and symbols) in the political context of the Bolivian « refounding » of the State and nation.